Nanohybrid structure analysis and biomolecule release behavior of polysaccharide-CDHA drug carriers - Huang, Li-Ying (Springer, 2013)
Nanoscaled polymer composites were prepared from polysaccharide chitosan (CS) and Ca-deficient hydroxyapatite (CDHA). CS-CDHA nanocomposites were synthesized by in situ precipitation at pH 9, and the CS-CDHA carriers were then fabricated by ionic cross-linking methods using tripolyphosphate and chemical cross-linking methods by glutaraldehyde and genipin. Certain biomolecules such as vitamin B(12), cytochrome c, and bovine serum albumin were loaded into the CS-CDHA carriers, and their release behaviors were investigated. Furthermore, these CS-CDHA carriers were examined by transmission electron microscopy, electron spectroscopy for chemical analysis, and X-ray diffraction. The release behavior of the biomolecules was controlled by the CS/CDHA ratios and cross-linked agents. By increasing the concentration of CS and the concentration of the cross-linking agents, cross-linking within carriers increases, and the release rate of the biomolecules is decreased. Moreover, the release rate of the biomolecules from the CS-CDHA carriers at pH 4 was higher than that at pH 10, displaying a pH-sensitive behavior. Therefore, these CS-CDHA hydrogel beads may be useful for intelligent drug release and accelerate bone reconstruction.